A Qualitative Study On Exploring The Perception And Motivation Of Cannabis Use Among Malaysian Graduates - Govarthnapany, Neshalatha (2019)
The objectives of the study includes understanding the motivation of cannabis use among young educated adults in Malaysia, to gain an understanding on the contextual use of cannabis among these users and to study the perception towards cannabis use and its related issues. There were in total 23 participants recruited in this study through snowball sampling. These participants are all Malaysians and have a minimum qualification of a bachelor’s degree. The methodology used in this study was the Interpretative Phenomelogical Analysis (IPA). The mean age of the study sample is 34.5 years old. Each participants were interviewed individually face-to-face or by phone. The findings of the study focused on the background of cannabis use, experience and reason of use, perception on cannabis-related issues and their hopes for the future. These study participants reported to use cannabis recreational and medicinal purposes. Nine master themes emerged from the findings: The purpose of cannabis use, Effects of cannabis use, Experience with other substances, Defaulted conventional drug treatment, Dependency, Cannabis acceptance in Malaysia, Cannabis acceptance in other countries, Cannabis legislation in Malaysia and Cannabis use in Malaysia in the Future. Participants of this study generally regarded cannabis to be a beneficial plant rather than regarding it as a drug. Although forbidden by the law, these participants are willing to take the risk to explore cannabis and it’s potential.